Respuesta :

Answer:

26x + 12y + 10z - 12

Step-by-step explanation:

1. Distribute

-4 times 7x = -28x

       Negative times a positive equals negative

-4 times -3y = 12y

-4 times -z = 4z

      Negative times a negative equal positive

-6 times 9x = 54x

-6 times -z = 6z

-6 times 2 = -12

to get a total of

-28x + 12y + 4z + 54x + 6z - 12

2. Combine like terms

(all z's, y's, x's and constants (1,2,3)

54x - 28x = 26x

4z + 6z = 10z

12y

-12

to get the final answer

26x + 12y + 10z - 12

ACCESS MORE